The Influence of Product Knowledge, Health Consciousness, and Price Affordability on the Intention to Purchase Organic Chicken in Malang City - Muhammad Raihan; Siti Azizah; Mohamed Shakal; Siti Nurul Kamaliyah; Hanief Eko Sulistyo (Journal of Agriprecision & Social Impact, 2026)
The growing trend toward a healthy lifestyle has driven increased consumer interest in organic food products, including organic chicken. This study aims to analyze the influence of product knowledge, health consciousness, and price affordability on the intention to purchase organic chicken in Malang City. Data were collected from 100 respondents using a structured Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics 22. The study population consisted of the general public in Malang City who serve as household food purchase decision-makers, with sampling conducted using the Proportionate Stratified Random Sampling technique across five subdistricts. The results showed that health consciousness and price affordability had a positive and significant effect on purchase intention (Sig. 0.000), whereas product knowledge did not have a significant effect on purchase intention (Sig. 0.967). This indicates that consumers rely more on health-oriented motivations than on technical product knowledge. An Adjusted R-Square value of 0.741 indicates that the three independent variables collectively explain 74.1% of the variation in purchase intention. These findings reveal that the organic chicken market in Malang is a niche market driven primarily by families with stable incomes and young, independent consumers. The practical implications of this study emphasize the importance of expanding product distribution and implementing health-value-based marketing communication strategies to convert consumer hesitation into actual purchase intent.